Net-Zero Energy Building – Case Study Al Khobar City, Saudi Arabia - Nader, Nader A; Alsayed, Rami S (International Journal of Sustainable Energy and Environmental Research, 2016)
The main goal of the proposed project is to demonstrate that considerable energy conservation can be done in residential building area in the KSA, considering the living conditions of house users. For this purpose, several houses will be tested using sizable Building Integrated PV (BIPV) system. In addition, the energy needs per year for each household will be covered in this study. Moreover, the proposed BIPV system will supply sufficient amount of electrical energy to allow free daily commute for homeowner (max. 60 km a day) with use of the electric car. The results indicate that the use of an insulation layer (BioPCM material) in building structure will decrease significantly the cooling capacity by 20%. The addition of solar hybrid air conditioner system improved the EER by 5.41% and the COP by 12.24 %. Finally, the installation plan for the PV panels in each residential household is in agreement with the official KSA government policy.